Sprucing up Himati designing content for an interactive student magazine - Boga, Jesse Ramon P.
Himati, the official student publication of the University of the Philippines Mindanao, is going through tough times: it is not efficiently working as the students' watchdog as manifested in the decline of frequent and timely publication, and inconsistency of design and undefined content over the past five years. It is not adapted with the changing times where student publications have a new role. More than reporting events and occurrences, they are now avenues for creative, analytical and critical discussion; and they are media that involve readers at large. What Himati needs to get back on its feet is a certain design and a unique mixture of content (called ?formula?) to follow. Both should be versatile enough to accommodate variety but can also be consistent for coherent publication in the long run. The primary focus of this study is to redesign Himati and define its formula. More specifically, this study aims to answer the question, ?What content, to be supplemented with a 'working design is most appropriate for Himati?? to find out what content fits Himati and its audience best is what makes a student publication successful. To do this, the researcher first identified the needs and reading interests of the students. A survey was conducted, with questions based on the Uses and Gratification Theory, which states that media is used by contemporary consumers to fulfill five needs: cognitive, affective, personal, social, and tension release. Survey results indicate that the previous issues of Himati do not express the common interest of students, who are more interested to read features-based articles. From there, the researcher crafted concepts for magazine contents that are dominantly features, which expressed a common interest of the students ? not too heavy and serious but sensible and fun. The researcher named the two major categories of the magazine: 'Radar' (editorial section containing news and opinion) and 'Campus Life' (features). Both are broad enough to cover an extensive range of topics at different angles, yet still specific enough as so not to confuse the readers. The design for the magazine's layout used recurring elements like endmarks, specific fonts and color accents. These elements make the design coherent, but still flexible enough to be varied and edited for future use. The end product of this production thesis, a Himati prototype, is a guideline for the publication's staff and is a means of keeping up with the changing times; it is designed to find a common ground among the readers' interests, and between the student publication's roles: to be a watchdog (to inform and to educate) and to give the students a sense of community (and publication ownership). After doing this study, which only focused on design and magazine content, the researcher finds that more intensive and comprehensive readership surveys and studies should be conducted in the near future
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts